Experimental setup and testing of an in-field system for real-time occupant feedback. Issue 4 (September 2019) - Lassen, N; Josefsen, T
Abstract: Thermal comfort and air quality in buildings have been found to be the 2nd and 5th largest sources of complaints among occupants in modern office buildings. In building operation, the determination of control setpoints is normally based on a combination of theoretical models and feedback from occupants. The feedback is most often unstructured and based on face-to-face information transfer, costing time for building operators and with no possibility for systematic learning over time. In practice, operating temperature ranges as small as 1-2°C are usually adopted in order to prevent complaints from occupants in office buildings. Research has however shown that narrow temperature ranges do not result in higher occupant satisfaction, and several researchers have proposed that control of buildings should be done based on continuous subjective feedback from the occupants in the building. This article covers the design and proof of concept for a non-intrusive system for continuous occupant feedback in offices. The system consists of a feedback terminal for capturing day-to day overall satisfaction with indoor climate, a smart phone based system for capturing personal comfort thresholds, and physical measurements of room temperature and CO2 level. Longitudinal tests were conducted in selected rooms in two buildings near Oslo in Norway, measuring a total of 20 office desks in regular use over 3-5 months. The findings indicate that this simple and inexpensive system collects information about the occupant's perception of the indoor climate. Further work must be done to give this information value for building control and learning.